0507 Mobile Cognitive Behavioral Therapy is Efficient in Improving Sleep in Students. (27th May 2020) - Eyal, S; Altman, Y; Baharav, A
Abstract: Introduction: Academic achievements and social life on campus represent the main focus for students, while sleep is neglected. The emergence of social media, gaming reduces sleep opportunity, quality and ability. Students are sleep challenged and prone to develop chronic sleep difficulties in later life. Cognitive behavioral interventions are recognized as effective for insomnia and circadian misalignment. We aimed at detecting sleep difficulties, related habits, and at testing the efficacy of a mobile app in improving sleep in students with insomnia symptoms. Methods: Observational study of US students who approached wellness staff and were offered the Refresh by Sleeprate mobile app that provides a sleep assessment followed by weekly cycles of personalized digital cognitive and behavioral reframing. The app collects perceived, and optional objective sleep data acquired using wearable devices. 892 students aged 18-30 years registered an account between Jan 1 and Oct 30, 2019. The study reports engagement data and outcomes of the assessment and the digital intervention. Results: 507 completed their assessment (6.2 avg nights). 69% presented insomnia symptoms with or without circadian misalignment, 8% circadian misalignment, 12% sleep deprivation, 11% poor sleep hygiene. 192 (55.3% of students with insomnia symptoms) completed at least one week of intervention (5.6 weekly avg nights, 28 avg total nights). Sleep Latency (SL) in minutes decreased from 28.8 (21.5) (Mean/SD) to 22.1 (19.3), p<0.001. When the initial mean SL was longer than 30 minutes, the improvement was larger, from 53.9 (20.8) to 32.7 (25.4) (p<0.001). Mean perceived Wake After Sleep Onset (WASO) longer than 30 minutes decreased from 46.3 (19.0) to 35.8 (21.4), p<0.05. Sleep Efficiency (SE) increased by 1.6% (p<0.002) for all, and by 7.1% (p<0.001) for SE<85%. Conclusion: The mobile app used reveals sleep problems and is efficient in improving insomnia symptoms in those who remain engaged. 55% of those who started the program also completed it. Engagement remains the main barrier to sleep improvement at scale. Support: N/A